Growth, physiology, and stomatal parameters of plant polyploids grown under ice age, present-day, and future CO2 concentrations - Šmarda, Petr; Klem, Karel; Knápek, Ondřej; Veselá, Barbora; Veselá, Kristýna; Holub, Petr; Kuchař, Vít; Šilerová, Alexandra; Horová, Lucie; Bureš, Petr (The New phytologist, 2023)
Polyploidy plays an important role in plant evolution, but knowledge of its eco-physiological consequences, such as of the putatively enlarged stomata of polyploid plants, remains limited. Enlarged stomata should disadvantage polyploids at low CO2 concentrations (namely during the Quaternary glacial periods) because larger stomata are viewed as less effective at CO2 uptake. We observed the growth, physiology, and epidermal cell features of 15 diploids and their polyploid relatives cultivated under glacial, present-day, and potential future atmospheric CO2 concentrations (200, 400, and 800 ppm respectively). We demonstrated some well-known polyploidy effects, such as faster growth and larger leaves, seeds, stomata, and other epidermal cells. The stomata of polyploids, however, tended to be more elongated than those of diploids, and contrary to common belief, they had no negative effect on the CO2 uptake capacity of polyploids. Moreover, polyploids grew comparatively better than diploids even at low, glacial CO2 concentrations. Higher polyploids with large genomes also showed increased operational stomatal conductance and consequently, a lower water-use efficiency. Our results point to a possible decrease in growth superiority of polyploids over diploids in a current and future high CO2 climatic scenarios, as well as the possible water and/or nutrient dependency of higher polyploids.
Keywords: Photosynthesis; Plant Leaves; oxid uhličitý; atmospheric carbon dioxide; stomatal conductance; photosynthesis; průduchy rostlin; Water; Carbon Dioxide; glacial periods; cell size; climate change; genome size; fotosyntéza; voda; listy rostlin; Plant Stomata; polyploidy